2010
DOI: 10.1111/j.2042-3306.2010.00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cardiovascular function and quality of recovery in isoflurane‐anaesthetised horses administered a constant rate infusion of lidocaine or lidocaine and medetomidine during elective surgery

Abstract: The combination of an intraoperative constant rate infusion of lidocaine and medetomidine did not adversely affect cardiovascular function in isoflurane-anaesthetised horses and improved the quality of recovery when compared to an intraoperative infusion of lidocaine alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 34 publications
2
35
0
4
Order By: Relevance
“…However, the time for the animals to remain standing was longer compared with lidocaine alone, whereas this authors assign this improved effect to the sedative effects of medetomidine. When fentanyl is used in sheep at a dose of 10 μg/ kg i.v., sedation continues for 60 minutes after its administration (WATERMAN; LIVINGSTON; AMIN, 1990), although one case of prolonged recovery has also been reported (kRONEN et al, 2005). Analyzing the results of these authors, it is possible that the residual sedative and analgesic effects of fentanyl (HUGHES; NOLAN, 1999) may have influenced the scores observed in the GPFL group because no signs of excitation were observed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the time for the animals to remain standing was longer compared with lidocaine alone, whereas this authors assign this improved effect to the sedative effects of medetomidine. When fentanyl is used in sheep at a dose of 10 μg/ kg i.v., sedation continues for 60 minutes after its administration (WATERMAN; LIVINGSTON; AMIN, 1990), although one case of prolonged recovery has also been reported (kRONEN et al, 2005). Analyzing the results of these authors, it is possible that the residual sedative and analgesic effects of fentanyl (HUGHES; NOLAN, 1999) may have influenced the scores observed in the GPFL group because no signs of excitation were observed.…”
Section: Discussionmentioning
confidence: 99%
“…An intraoperative CRI of lidocaine (50 μg/kg/minute) induces ataxia and a poor quality of recovery in horses; thus, it is necessary to discontinue the infusion 30 minutes before the end of surgery (VALVERDE et al, 2005). In horses, Valverde et al (2010) reported that the combination of a CRI of lidocaine and medetomidine induces better recovery quality scores. However, the time for the animals to remain standing was longer compared with lidocaine alone, whereas this authors assign this improved effect to the sedative effects of medetomidine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Driessen (2005) reviewed early the potential of IV lidocaine CRI for equine PIVA and presented some personal experience with a reduced infusion rate (1.8 mg kg -1 h -1 ) compared to previous publications (Doherty und Frazier 1998, Dzikiti et al 2003) that used 3 to 6 mg kg -1 h -1 . Further investigations confirmed the ability of systemic administration of lidocaine to decrease dose-dependently anaesthetic requirements during general anaesthesia in horses , Valverde et al 2010) without intra-anaesthetic physiological or metabolic adverse effects (Valverde et al 2010, but with the risk at the recommended dosage (3 mg kg -1 h -1 ) to develop high plasma levels under general anaesthesia (Feary et al 2005) and poor quality of the recovery phase , Valverde et al 2010). To our knowledge at the moment this study was performed, there were only two trials performed to compare the administration of lidocaine to a control group in a clinical setting (Dzikiti et al 2003, but using high dose of lidocaine and with different recovery methods.…”
Section: Introductionmentioning
confidence: 94%